2009
DOI: 10.1002/ajpa.21161
|View full text |Cite
|
Sign up to set email alerts
|

Population relationships in the Mediterranean revealed by autosomal genetic data (Alu and Alu/STR compound systems)

Abstract: The variation of 18 Alu polymorphisms and 3 linked STRs was determined in 1,831 individuals from 15 Mediterranean populations to analyze the relationships between human groups in this geographical region and provide a complementary perspective to information from studies based on uniparental markers. Patterns of population diversity revealed by the two kinds of markers examined were different from one another, likely in relation to their different mutation rates. Therefore, while the Alu biallelic variation un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 48 publications
5
30
0
Order By: Relevance
“…To illustrate this, the CD4 100(+), a common Sub-Saharan African haplotype, has been found in the Libyan sample with a frequency of 0.0327. This genetic richness of the Libyan population, also stated in previous work (Ben Cherni et al, 2011;Fadhlaoui-Zid et al, 2011), could be due Present study Flores et al, 2000;González-Pérez et al, 2010 partly to the fact that Libya is located more in the south (in continuity with the south of Tunisia) nearer to central Sub-Saharan countries and at the same time it has a long Mediterranean coastline to the north. Regarding the genetic relationships among Middle East and North African samples, if we exclude the Libyan sample, we do not observe any particular genetic closeness among these groups.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…To illustrate this, the CD4 100(+), a common Sub-Saharan African haplotype, has been found in the Libyan sample with a frequency of 0.0327. This genetic richness of the Libyan population, also stated in previous work (Ben Cherni et al, 2011;Fadhlaoui-Zid et al, 2011), could be due Present study Flores et al, 2000;González-Pérez et al, 2010 partly to the fact that Libya is located more in the south (in continuity with the south of Tunisia) nearer to central Sub-Saharan countries and at the same time it has a long Mediterranean coastline to the north. Regarding the genetic relationships among Middle East and North African samples, if we exclude the Libyan sample, we do not observe any particular genetic closeness among these groups.…”
Section: Discussionsupporting
confidence: 72%
“…This combination is absent in Sub-Saharan African and European samples except in some Mediterranean groups from Spain, Sardinia and Sicily. It was proposed in previous works (Flores et al, 2000;González-Pérez et al, 2010) to be representative of an ancient Berber background because it was observed throughout North Africa. However, its presence in Bahrain and southern Iran makes a new interpretation necessary: this haplotype could be a common haplotype of those human groups from the Middle East that colonized the southern shore of the Mediterranean in the Upper Paleolithic, if we take into account that its estimated age is around 36000 BP (95% CI: 3200-186000; González-Pérez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When considering a dendrogram constructed based on the allele frequencies, two clusters were clearly formed, in which five Asian populations (Japanese, Northern Han, Hui, Uygur, and Kazakh) were presented in one cluster, while two Europeans and one West Asian (Italian, Greek, and Saudi Arabian) were presented in another. Gonzalez-Perez et al [11] analyzed the population relationships in the Mediterranean populations by using the combination of genetic markers; 18 Alu insertion polymorphisms (polymorphisms based on the presence and absence of an Alu element at a specific location of chromosome) and 3 STR loci. The results showed that, when considering the Alu/STR haplotype frequencies, the differentiation between Northern and Southern Mediterraneans was significantly noticeable.…”
Section: Introductionmentioning
confidence: 99%